A Brief Overview of National Languages in Mauritania - Naciri-Azzouz, Amina (Africana Studia, 2024)
The aim of this note is to present a brief approach of the national languages in Mauritania based on a literature review which shows how ethnic tensions have been at the heart of the country’s linguistic and educational policy: an issue still relevant today. For this purpose, the status of Mauritanian languages in relation to other neighboring countries is first presented. Secondly, the sociolinguistic situation in Mauritania is discussed, underlining a diversity of linguistic and social practices. A third point addresses the historical overview of the linguistic and educational reforms of the country (which have always focused on Arabic and French downsizing national languages such as Pulaar, Wolof and Soninké) is given. Finally, the dynamism and the complexity of linguistic practices in Mauritania, as well as their social significance, are highlighted, a reality that is not always reflected in the linguistic policies. Keywords: Language Policy, National Languages, Mauritania.